Efektivitas Konten Dakwah di Media Televisi: Perspektif Masyarakat Terhadap Acara Ceramah Ustadz - Najla Aqilah Halim; Tengku Walisyah (Universitas Cokroaminoto Yogyakarta, 2027)
This study aims to analyze the effectiveness of Islamic preaching content on television based on rural community perspectives on television sermons. The study used qualitative methods with a phenomenological approach through interviews with ten informants in Gang Amaliyah, Laudendang District. The results indicate that television remains effective as a medium for Islamic preaching for the elderly and housewives due to its ease of access and trust, while the younger generation tends to shift to digital media. Television Islamic preaching plays an important role in enhancing religious and moral understanding, but presentation innovation is needed to remain relevant in the digital era and attract the interest of all levels of society. This study, using a phenomenological approach, examines the perspectives of local communities across generations regarding innovations in television Islamic preaching in the digital era.